Matter non-conservation in the universe and dynamical dark energy - Fritzsch, Harald. (2013)
In an expanding universe, the vacuum energy density ρ Λ is expected to be a dynamical quantity. In quantum field theory in curved spacetime, ρ Λ should exhibit a slow evolution, determined by the expansion rate of the universe H. Recent measurements on the time variation of the fine-structure constant and of the proton-electron mass ratio suggest that the basic quantities of the standard model, such as the QCD scale parameter Λ QCD, may not be conserved in the course of the cosmological evolution. The masses of the nucleons m N and of the atomic nuclei would also be affected. Matter is not conserved in such a universe. These measurements can be interpreted as a leakage of matter into vacuum or vice versa. We point out that the amount of leakage necessary to explain the measured value of ṁN/mN could be of the same order of magnitude as the observationally allowed value of ṗΛ/ρΛ, with a possible contribution from the dark matter particles. The dark energy in our universe could be the dynamical vacuum energy in interaction with ordinary baryonic matter as well as with dark matter.